2011
DOI: 10.1177/0960327111407644
|View full text |Cite|
|
Sign up to set email alerts
|

Infant mortality rates regressed against number of vaccine doses routinely given: Is there a biochemical or synergistic toxicity?

Abstract: The infant mortality rate (IMR) is one of the most important indicators of the socio-economic well-being and public health conditions of a country. The US childhood immunization schedule specifies 26 vaccine doses for infants aged less than 1 year—the most in the world—yet 33 nations have lower IMRs. Using linear regression, the immunization schedules of these 34 nations were examined and a correlation coefficient of r = 0.70 ( p < 0.0001) was found between IMRs and the number of vaccine doses rout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 16 publications
4
41
1
Order By: Relevance
“…This explains sudden death from snake bites [321,322], vaccines [323][324][325][326][327][328][329][330][331][332][333], and cocaine [215], in otherwise healthy people, as examples. Depending on their surfactant property and their position within the Hofmeister series, environmental biological or chemical intoxicants of virtually any type can provide the EIWS to induce SDS.…”
Section: Discussionmentioning
confidence: 99%
“…This explains sudden death from snake bites [321,322], vaccines [323][324][325][326][327][328][329][330][331][332][333], and cocaine [215], in otherwise healthy people, as examples. Depending on their surfactant property and their position within the Hofmeister series, environmental biological or chemical intoxicants of virtually any type can provide the EIWS to induce SDS.…”
Section: Discussionmentioning
confidence: 99%
“…When stratified by year, there was no correlation in hospitalization rates ( r 2  = 0.03) and a weak correlation in mortality rates ( r 2  = 0.40) during the studied time period, 1990–2010. The mean hospitalization rates in VAERS for the period 1990–2000 and 2001–2010 were 15.8% (3219 of 20,377) and 16.6% (3060 of 18,424), respectively.…”
Section: Resultsmentioning
confidence: 83%
“…Linear regression analysis of hospitalization rates as a function of (a) the number of reported vaccine doses and (b) patient age yielded a linear relationship with r 2  = 0.91 and r 2  = 0.95, respectively (Figures 3 and 4). The hospitalization rate increased linearly from 11.0% (107 of 969) for 2 doses to 23.5% (661 of 2817) for 8 doses (Table 2), and decreased linearly from 20.1% (154 of 765) for children aged <0.1 year to 10.7% (86 of 801) for children aged 0.9 year (Table 3).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In the first five countries such as Singapore (2.31), Sweden (2.75), Japan (2.79), Iceland (3.23) and France (3.33) only 12 vaccine doses and in the US, 26 vaccine doses are given to infants during the first year of life. High rate of infant mortality have been reported between the ages of 2 to 4 months (the highest rate of vaccination) especially when the first doses of DPT vaccine were given to infants [18,19]. Evaluation of a mathematical model of the 2009 H1N1 influenza pandemic in Mexico in six age groups (0-5 yr, 6-12 yr, 13-19 yr, 20-39 yr, 40-59 yr, ≥ 60 yr) has revealed that the optimal age groups for vaccination against the disease were young adults (20-39 yr) followed by school age children (6-12 yr) [20].…”
Section: Increase In Infant Mortality Ratementioning
confidence: 99%